Intent disclosure in late-life suicide: Age group differences in correlates and associations with suicide means - Choi, Namkee G.; Marti, C. Nathan (Frontiers in Psychology, 2022)
Age-adjusted suicide rates declined from 2018 to 2020. However, suicide rates among older adults, particularly males 75 and older, have continued to rise, and the evidence base for effective interventions to prevent suicide in late life remains limited. One strategy to prevent older adults’ suicidal behavior is to intervene when they reveal suicide intent. Previous research found that a significant proportion of older suicide decedents disclosed their suicide intent close to the fatal incident. In this study, based on the 2017–2019 US National Violent Death Reporting System (NVDRS) data, we examined: (1) correlates of intent disclosure among three age groups (65-74, 75-84, and 85+) of older suicide decedents (N = 17,917; 14,856 men and 3,061 women); and (2) associations of suicide means with intent disclosure and suicide contributing factors. The results show that 19.9% of all suicide decedents aged 65+ (18.7%, 21.0%, and 22.0% in the 65-74, 75-84, and 85+ age groups, respectively) disclosed their suicide intent to their partner, family/friends, and healthcare providers within a month of their death. Multivariable analyses using generalized linear models for a Poisson distribution with a log link showed that physical and mental health, substance misuse, addiction problems, and relationship/other life stressors were associated with a higher likelihood of intent disclosure in the 65-74 and 75-84 age groups. However, only physical health problems were associated with a higher likelihood of intent disclosure among those aged 85 and older. Intent disclosure was not associated with using firearms and poisoning as suicide means but with a lower likelihood of hanging or suffocation. Mental health and substance misuse problems were associated with higher odds of hanging or suffocation and poisoning, and physical health problems and male sex in the 85+ age group were associated with higher odds of firearm use. Suicide prevention strategies for those who have disclosed their suicide intent or are at risk of suicidal behavior should include more patient-centered comfort and palliative care, mental health/substance misuse/addiction treatment, and restriction of access to potential suicide means. More research on older adults who disclose suicide intent and late-life suicide prevention strategies is needed.